Akibat Hukum Terhadap Pelaksanaan Arisan Online Berdasarkan Undang-Undang Nomor 19 Tahun 2016 - Erlin Kusnia Dewi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
The 2008 ITE Law regulates fraudulent acts that are applied online. The researcher wrote a scientific article with the title Legal Impacts on the Implementation of Online Arisan Based on Law No. 19 of 2016. There are two formulations of this research problem How is the Legal Protection for Parties Conducting Online Arisan based on Law Number 19 of 2016? and What are the Criminal Sanctions Against BandarArisanOnlinein the event of Default? Normative legal research is a method applied by the author in this scientific article. The author carries out a literature study by collecting legal material to answer the formulation of research problems. The author carries out a literature study by collecting legal material to answer the formulation of research problems. This study's findings explain that there are legal protections for parties who carry out online social gathering criminal sanctions against online social gathering based on ITE Law No. 19 of 2016 against online social gathering fraud perpetrators focused on individual legal subjects. This finding is supported by Article 28 paragraph (1), which explains that consumers who get losses due to online transactions can obtain legal protection.